Diagnostic Yield of Extended Cardiac Patch Monitoring in Patients with Stroke or TIA - Tung, Christie E.; Su, Derek; Turakhia, Mintu P.; Lansberg, Maarten G. (Frontiers in Neurology, 2015)
Background: It is important to evaluate patients with TIA or stroke for atrial fibrillation (AF) because the detection of AF changes the recommended anti-thrombotic regimen from treatment with an antiplatelet agent to oral anticoagulation. This study describes the diagnostic yield of a patch-based, single-use, and water-resistant 14-day continuous cardiac rhythm monitor (ZIO Patch) in patients with stroke or TIA. Methods: We obtained data from the manufacturer and servicer of the ZIO Patch (iRhythm Technologies). Patients who were monitored between January 2012 and June 2013 and whose indication for monitoring was TIA or stroke were included. The duration of monitoring, the number and type of arrhythmias, and the time to first arrhythmia were documented. Results: 1,171 monitoring reports were analyzed. The mean monitor wear time was 10.9 days and the median wear time was 13.0 days (interquartile range 7.2-14.0). The median analyzable time relative to the total wear time was 98.7% (IQR 96.0-99.5%). AF was present in 5.0% of all reports. The mean duration before the first episode of paroxysmal AF (PAF) was 1.5 days and the median duration was 0.4 days. 14.3% of first PAF episodes occurred after 48 hours. The mean PAF burden was 12.7% of the total monitoring duration. Conclusion: Excellent quality of the recordings and very good patient compliance coupled with a substantial proportion of AF detection beyond the first 48 hours of monitoring suggest that the cardiac patch is superior to conventional 48-hour Holter monitors for AF detection in patients with stroke or TIA.